A Review: The Role of Electrical Resistivity in Groundwater Exploration and Management - Charles Olubunmi Ogunkoya (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
The review paper explores the use of electrical resistivity techniques to explore and manage groundwater, providing vital insights into aquifer properties and the behavior of groundwater. It delves into the principles and applications, limitations, and potential future developments. Groundwater is a very important water source for sustainable development, especially in dry areas thereby making effective groundwater exploration essential. Geophysical techniques like vertical electrical resistivity soundings (VES) and electrical resistivity tomography (ERT) are some of the methods used in analyzing subsurface characteristics and the behavior of aquifers. These methods allow the identification of hydrogeological parameters such as water saturation, porosity, and aquifer boundaries. This article further explores how instrumentation advancements, machine learning, and integrated approaches also improve accuracy in subsurface imaging despite geological complexities and interpretation ambiguities. The resistivity methods have proven effective in coastal aquifers, detecting saltwater intrusion, and monitoring groundwater quality.